Dissemination of BARI released potato varieties in Rangpur region of Bangladesh (Progressive Agriculture, 2021)
The experiment was conducted during rabi season 2019-2020 at Rangpur and Kurigram districts under Agricultural Research Station, On Farm Research Division, Alamnagar, Rangpur to promote and disseminate newly released potato variety, BARI Alu-35, BARI Alu-36, BARI Alu-37, BARI Alu-40 and BARI Alu-41among the potato growers of Rangpur sadar Upzilla in Rangpur and Chilmari Upazilla in Kurigram. The experiment was arranged in a randomized complete block design (RCBD) with four dispersed replications. The treatments included T1: BARI Alu-35, T2: BARI Alu-36, T3: BARI Alu-37, T4: BARI Alu-40 and T5: BARI Alu-41. BARI Alu-41 showed excellent performance and higher yield followed by BARI Alu-40 and BARI Alu-36. Farmers were happy to observe the performance of the varieties and demanded quality seed for next year cultivation. The highest common scab infection was observed in (BARI Alu-35) (1.62%) where the lowest in BARI Alu-41. Maximum virus infected was found in BARI Alu-40 (2.29%), where the lowest infection was observed in BARI Alu-41 (1.22%).Progressive Agriculture 32 (1): 17-21, 2021